Method of non-contact remote determination of the current functional state of the athlete - Artemiev, V.; Druz, V.; Yefremenko, A. (Slobozhanskyi herald of science and sport, 2020)
Purpose: development of a non-contact method for monitoring the current functional state in the process of the direct implementation of professional activities.